Response of paddy (Oryza sativa) to exogenous application of bio-regulators in soils irrigated with alkali groundwater - BALI, A; SINGH, AWTAR; MINHAS, P S; YADAV, R K (The Indian Journal of Agricultural Sciences, 2020)
Exogenous applications of plant bio-regulators (PBRs) were evaluated during kharif of 2017 and 2018 for their efficiency to facilitate growth and production processes in paddy (Oryza sativa L.) grown in loam soils undergoing sodification (pHs 8.5 & 8.3; ESP 37 & 13) with alkali groundwater irrigation (RSC 3.4 meq L-1 at site-I during both the years and RSC 4.4 & 3.7 meq l-1 at site-II during 2017 and 2018, respectively). The PBRs included gibberellic acid (GA, 25 ppm), potassium nitrate (PN, 15 g l-1), salicylic acid (SA, 10uM), sodium benzoate (SB, 150 mg l-1; 2017 only) and thio-urea (TU, 500 ppm). These were sprayed at three stages, i.e. seedling establishment and tillering (30-40 days after transplanting), booting and maximum growth (50-60 DAT) and flowering and grain formation (80-90 DAT). PBRs promoted growth and improved yields and contributing attributes like tillers, panicle length and filled grains. The increase in grain yield equaled 20, 16, 2, 16 and 24% with application of GA, PN, SA, SB and TU, respectively at Site-I during 2017 and the counter values at Site-II were 4, 24, 2, 17 and 21%. Similarly, during 2018, the improvements in yield equaled 3, 15, 4 and 20% with GA, PN, SA and TU at Site-I and nil, 14, 8 and 7% at Site- II, respectively. The Na:K ratio was lower especially with PN while grain quality monitored in terms of protein and gluten contents remained unaffected. On the basis of consistency, it emerges that the use of thio-urea and potassium nitrate is a viable option for alleviating sodicity stress in paddy under alkali groundwater irrigated conditions.